Revisioning India's North-East through the Look East Policy - Mazumdar, Sayantani Sen, (Brill | Manohar Publishers & Distributors, 2018)
North-East India is the epitome of diverse and rich cultural heritage of India and has the credibility of being the harbinger of economic progress through a comprehensive manoeuvring of cultural exchanges with South-East Asian neighbours. The inherent potential and the prospects are adequately nurtured and utilized by India's Look East Policy for a better future of the region. This book proposes to contextualize and inquire into the development of the North East of India with reference to the Look East policy. This volume is the outcome of more than eight years study on India's Look East Policy and its implications on the North-East region and is indispensable for scholars working on South-East Asia.